1997
DOI: 10.1063/1.365989
|View full text |Cite
|
Sign up to set email alerts
|

Relative sensitivity of photomodulated reflectance and photothermal infrared radiometry to thermal and carrier plasma waves in semiconductors

Abstract: Articles you may be interested inSemiconductor microwave mirror for a measurement of the dynamical Casimir effect Rev. Sci. Instrum. 75, 4967 (2004); 10.1063/1.1808892Carrier-density-wave transport property depth profilometry using spectroscopic photothermal radiometry of silicon wafers I: Theoretical aspects J. Appl. Phys. 93, 5236 (2003); 10.1063/1.1565498Carrier-density-wave transport property depth profilometry using spectroscopic photothermal radiometry of silicon wafers II: Experimental and computational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 22 publications
1
27
0
1
Order By: Relevance
“…(1). It turns that the thermal component C t is proportional to the infrared absorption coe− fficient [11]. In the frame of the classical Drude theory the infrared absorption coefficient is proportional to the carrier concentration N. Hence, the thermal−to−plasma component coefficient A is proportional to the carrier concentration N. The observed linear relation between the carrier concentra− tion and the thermal−to−plasma component coefficient, as well as the estimated value of hole diffusion length in CdSe indicate that it is possible to estimate the carrier recombina− tion lifetime as short as 0.1 μs by PTR method at fre− quencies below the characteristic knee.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(1). It turns that the thermal component C t is proportional to the infrared absorption coe− fficient [11]. In the frame of the classical Drude theory the infrared absorption coefficient is proportional to the carrier concentration N. Hence, the thermal−to−plasma component coefficient A is proportional to the carrier concentration N. The observed linear relation between the carrier concentra− tion and the thermal−to−plasma component coefficient, as well as the estimated value of hole diffusion length in CdSe indicate that it is possible to estimate the carrier recombina− tion lifetime as short as 0.1 μs by PTR method at fre− quencies below the characteristic knee.…”
Section: Resultsmentioning
confidence: 99%
“…It causes a modulation of the constant IR radiation of the sample being the result of a free carrier absorption of this radiation. In general the photothermal infrared radio− metry frequency signal is a sum of thermal and plasma components [11] …”
Section: Theoretical Model and Numerical Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Photothermal radiometry (PTR) is a non-contact method which enables to measure optical and thermal parameters of materials [1,2]. In the case of semiconductors, PTR additionally yields information about the recombination parameters [3,4]. Recently, it was found that for infrared (IR) semitransparent semiconductors, it is possible to obtain information on the carrier concentration with quantitative values after calibration to Hall carrier concentration [5].…”
Section: Introductionmentioning
confidence: 99%
“…Reviews of the subject matter have been presented by Mandelis [1] and Christofides et al [2]. The major advantage of PTR over other photothermal techniques, such as photomodulated thermoreflectance (PMOR), has been found to be the higher sensitivity of PTR to the photo-excited free carrier-density-wave (the modulated-laser driven oscillating electronic diffusionwave [3]) than PMOR [4,5]. This advantage exists due to domination of the free-carrier wave over the superposed thermal-wave (TW) contributions to the PTR signal.…”
Section: Introductionmentioning
confidence: 99%